Cassava technology assessment and transfer through users participation in India - Anantharaman, M.; Ramanathan, S. (International Center for Tropical Agriculture, 2001)
Cassava plays a major role in the food security of a large but weaker sector of the population, operating under complex, diverse and risk-prone farming systems. As the crop generally received low priority in the extension agenda of Government policies, direct intervention in the technology assessment and transfer by CTCRI in India was considered necessary. Over the past three decades the transfer of technology (TOT) program has undergone changes in concept and methodology according to changing farmers’ needs and socio-economic conditions, presently culminating in the concern for the users rather than the crop. CTCRI has implemented a series of “Users Participatory Programmes” in assessing and transferring the cassava technology. The assessment of cassava technology was done in various production systems, including hill agriculture, as well as users’ categories, including hill tribes. Agro-ecosystem analyses were conducted prior to the assessment of the cassava technologies; these were carried out in stages involving different categories of users. There were differential preferences observed in the various production systems as well as in the users’ categories. Trials conducted in the lowland production system indicated that the cassava varieties CI-649 and CI-731 were preferred, while farmers of upland production systems rated CI-732 and CI-649 as the best ones. Differences were also observed in the varietal preferences by various tribal people. The trials clearly indicate that there is a need to develop location-specific as well as user-specific technologies. The TOT programs excuted by CTCRI during the past three decades, namely the National Demonstrations, the Operational Research Project, and the Lab-to-Land Programme, and the impact of these programs are briefly described in the paper. The technology assessment and refinement through the Institution-Village-Linkage Programme (IVLP), a novel concept using a holistic approach, and the current testing and popularizing of cassava varieties in Tamil Nadu are detailed in the paper. The technology transfer is also enhanced through human resources development in participatory training courses and seminars. The issue of concern is who makes the choices of technology. Normally those least affected by the choice are the ones responsible for determining that choice, while those who are forced to live with the technology have least say in the matter. - Hoyzer, N.